IMPROVED RESOURCE AWARE HYBRID META-HEURISTIC ALGORITHM FOR TASK SCHEDULING IN CLOUD ENVIRONMENT - Gupta, D; Sidhu, H.J.S (International Journal of Computer Sciences and Engineering, 2025)
Popularity of services over cloud can be estimated from the fact that all major mobile and computer system manufacturers are providing free cloud services to their client on purchase of their product. Easy and fast access to internet services have resulted in increased usage of cloud infrastructure. Also, the amount of data being generated and shared over cloud has increased multi-folds. With ever increasing users, resource provider is aware that they cannot afford wastage or misutilization of its resources. Hence, selection of right resource for fulfilling the request of the customer is vital. Scheduling of tasks over cloud is a key research area. Meta-Heuristic algorithms provide efficient solution to this problem. But, each metaHeuristic algorithm individually suffers from inherent draw backs. So, there is a need to design a scheduling algorithm that does not suffer from the inherent draw backs of any individual meta-heuristic algorithm and is aware of the current utilization of resources in the cloud. In this paper, an improved resource aware hybrid meta-heuristic scheduling algorithm has been designed which reduces the overall Makespan time, Transfer cost and Response time. It also takes into consideration the current utilization of resources in the cloud.